Transgenic Strategies for Enhancement of Nematode Resistance in Plants - Ali, Muhammad A.; Azeem, Farrukh; Abbas, Amjad; Joyia, Faiz A.; Li, Hongjie; Dababat, Abdelfattah A. (Frontiers in Plant Science, 2017)
Plant parasitic nematodes (PPNs) are obligate biotrophic parasites causing serious damage and reduction in crop yields. Several economically important genera parasitize various crop plants. The root-knot, root lesion and cyst nematodes are the three most economically damaging genera of PPNs on crops within the family Heteroderidae. It is very important to devise various management strategies against PPNs in economical important crop plants. Genetic engineering has proven a promising tool for the development of biotic and abiotic stress tolerance in crop plants. Additionally, the genetic engineering leading to transgenic plants harbouring nematode resistance genes has demonstrated its significance in the field of plant nematology. Here, we have discussed the use of genetic engineering for the development of nematode resistance in plants. This review article also provides a detailed account of transgenic strategies for the resistance against PPNs. The strategies include natural resistance genes, cloning of proteinase inhibitor coding genes, anti-nematodal proteins and use of RNA interference to suppress nematode effectors. Furthermore, the manipulation of expression levels of genes induced and suppressed by nematodes has also been suggested as an innovative approach for inducing nematode resistance in plants. The information in this article will provide an array of possibilities to engineer resistance against PPNs in different crop plants.